The Incidence and Risk Factors Associated with Chronic Liver Enzyme Elevation (cLEE) in HIV-Monoinfected Persons. (4th October 2017) - Wood, Shannon; Byrne, Morgan; Deiss, Robert; Okulicz, Jason; O'Bryan, Thomas; Schofield, Christina; Ferguson, Tomas; Whitman, Timothy J; Agan, Brian; Ganesan, Anuradha
Abstract: Background: Chronic liver-associated enzyme elevations (cLEE) are common in persons with HIV; however, the significance in patients without hepatitis B or C co-infection remains unclear. The aims of this study were to evaluate the incidence and risk factors associated with cLEE in HIV-monoinfected subjects enrolled in the US Military HIV Natural History Study (NHS). Methods: We included NHS subjects who were HBV and HCV seronegative with follow-up after 1996. cLEE was defined as alanine amino transferase (ALT) levels ≥ 1.25x the upper limit of normal recorded at ≥ 2 visits spanning a period of 6 months within 2 years. Baseline characteristics between patients with and without cLEE were compared. Percentages are presented for categorical variables with medians and interquartile ranges presented for continuous variables. Multivariate Cox proportional hazards models were used to examine risk factors for cLEE. Results: Of 3, 163 included patients, 367 (11.7%) met criteria for cLEE. The incidence of cLEE was 1.4/100 person-years of follow-up (1.2-1.5) with a period prevalence of 35%. Significant differences in baseline characteristics between groups are tabulated below. The median time from HIV diagnosis to cLEE was 5 years (3-8) with the majority of ALT elevations categorized as grade 1 (40%). BMI was significantly associated with cLEE only in the unadjusted model. In an adjusted model, male gender (HR 1.7 [1.0–2.8]) and Hispanic/Other race (compared with Caucasians: HR 1.8 [1.3-2.5]) were associated with cLEE while African-American race was protective (compared with Caucasians: HR 0.75 [0.58–0.98]). The use of antiretroviral therapy [ART] (HR 1.9 [1.2-3.0]) and non-ART antiretrovirals (HR 2.0 [1.1-3.4]) were also associated with cLEE. Conclusion: cLEE is common in the NHS, although the incidence rate is lower than that reported in other cohorts. ART use was associated with cLEE emphasizing the need for surveillance of liver enzymes in patients on ART. The association between race and cLEE needs further evaluation. Disclosures: All authors: No reported disclosures.